Utility of cockroach as a model organism in the assessment of toxicological impacts of environmental pollutants (2022)
Environmental pollution is a global concern because of its associated risks to human health and ecosystem. The bio-monitoring of environmental health has attracted much attention in recent years and efforts to minimize environmental contamination as well as to delineate toxicological mechanisms related to toxic exposure are essential to improve the health conditions of both humans and animals. This review aims to substantiate the need and advantages in utilizing cockroaches as a complementary, non-mammalian model to further understand the noxious impact of environmental contaminants on humans and animals. We discuss recent advances in neuro- toxicology, immunotoxicology, reproductive and developmental toxicology, environmental forensic entomo- toxicology, and environmental toxicology that corroborate the utility of the cockroach (Periplaneta americana, Blaptica dubia, Blattella germanica and Nauphoeta cinerea) in addressing toxicological mechanisms as well as a sensor of environmental pollution. Indeed, recent improvements in behavioural assessment and the detection of potential biomarkers allow for the recognition of phenotypic alterations in cockroaches following exposure to toxic chemicals namely saxitoxin, methylmercury, polychlorinated biphenyls, electromagnetic fields, pharma- ceuticals, polycyclic aromatic hydrocarbon, chemical warfare agents and nanoparticles. The review provides a state-of-the-art update on the current utility of cockroach models in various aspects of toxicology as well as discusses the potential limitations and future perspectives.